Environmental DNA screening of Phocoenobacter atlanticus subsp. atlanticus in Atlantic salmon aquaculture - David A. Strand; Jannicke Wiik-Nielsen; Saima Mohammad; Hanne Nilsen; Bjarte Langhelle; Matilde Holmeset; Sonal Patel; Hanne Log Persson; Duncan Colquhoun (PLoS ONE, 2026)
There has been a drastic increase of pasteurellosis cases in Atlantic salmon aquaculture in Norway since 2018, caused by the bacterium Phocoenobacter atlanticus subsp. atlanticus , resulting in reduced animal welfare and increased mortalities. Early detection and identification of pathogens are crucial in intensive aquaculture to enable implementation of effective management and mitigation strategies. The increased application of environmental DNA (eDNA) monitoring in aquatic environments demonstrates the potential use for early detection of pathogens in aquaculture. In this study we investigated the usage of eDNA monitoring of Ph. atlanticus in Atlantic salmon aquaculture. We conducted a trial to investigate the effect of storage conditions and transport time on eDNA detection of Ph. atlanticus from water samples. We then conducted three field trials: a) to investigate the optimal sampling location for eDNA samples from farms with known Ph. atlanticus infection status, b) to screen farms presumed non-infected with Ph. atlanticus and c) to evaluate the eDNA detection in samples collected from anaesthetic tanks during lice counting. The storage trial revealed a reduction in Ph. atlanticus detection after one week at 4 °C or after two days at 22 °C. At farms with known Ph. atlanticus infection status we experienced poor detection of Ph. atlanticus from water samples collected in the net pen. However, samples collected from treatment water during thermal delousing revealed concentration of Ph. atlanticus during treatment, even in farms with negative net pen samples. Subsequent eDNA screening (sampling treatment water) of farms with presumed non-infected status, identified the presence of Ph. atlanticus in ~55% of the farms tested. Ph. atlanticus was also detected in water samples collected from anaesthetic tanks following lice counting. Our results demonstrate early detection of Ph. atlanticus, even in lowly prevalent populations, demonstrating the potential use of eDNA monitoring of pathogens in Atlantic salmon aquaculture.